The Particularity of the Quranic Words in translation: A Study on the Korean Translation of the Word “Wali: Guardian” - Ahmed, Mona Farouk (Arab Journal for Sciences and Research Publishing, 2020)
The Quran is the holy book of Islam which has been almost translated to all languages of the world. The translation of the words of God is a great work which include a responsibility of conveying the accurate meaning of God’s words. The researcher of this paper studied the Korean language and participated in Korean-Arabic translations over twenty years. Accordingly, the researcher felt the responsibility of which she tries through this paper to shed the light on the Korean translation of Quran hoping for reaching the most accurate translation for Quran. This paper focused on one word of the noble Quran, tracing the Korean translation to examine its accuracy as a sample of other words that may include difficulties in the Korean translation. The choice of the word “wali: Guardian” was based on its Islamic specificity and its possible impacts on the right understanding of Islam. The study began with the definition of the word and its Islamic particularity. Then, the study presented an analysis of the Korean translation of the word through exploring the Quranic verses containing the word. Finally, the study gave suggestions for the accurate translation of the word which would include recommendations for the future translation of Quran. * This work was supported by the Ministry of Education of the Republic of Korea and the National Research Foundation of Korea (NRF-2018S1A6A3A02022221). * هذا العمل مدعوم من وزارة التعليم الكورية والمعهد الكوري القومي للبحوث (NRF-2018S1A6A3A02022221).